Anaesthesia for bougie dilatation of subglottic stenosis: report of two cases - Raju, Athira; Chambath, Sooraj; Kannamadathy Poulose, Biji (International Journal of Research in Medical Sciences, 2023)
Subglottic stenosis is a rare but life-threatening condition characterized by narrowing of subglottis. Airway dilatation (balloon/bougie) has become very effective for correction of stenosis. Anaesthesia management for bougie or balloon dilatation of subglottic stenosis needs proper planning, team work and efficient utilization of resources. Airway management options include apneic pause technique, supraglottic jet ventilation, THRIVE (transnasal humidified rapid insufflation ventilatory exchange) and cardiopulmonary bypass/extracorporeal membrane oxygenation in emergency scenario. Total intravenous anaesthesia along with airway anaesthesia remains the best anesthetic management option as it provides excellent conditions for shared airway surgery.